Impact of Discharge Fluctuations on River Morphological Changes: A Case Study of the Palu River - Darwin Lion; Andi Rusdin; Zeffitni; Sri Warliawati (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
The Palu River is one of the major rivers in Central Sulawesi that has experienced significant morphological changes due to discharge fluctuations and sediment transport dynamics, particularly in the Kalukubula segment. These morphological changes directly reduce channel conveyance capacity and increase flood risk. This study aims to analyze sediment transport capacity and riverbed elevation changes induced by flow discharge fluctuations, as well as to evaluate the agreement between simulation results and actual field conditions. The research employs a quantitative approach based on one-dimensional numerical modeling using the HEC-RAS software. The data used include river topography surveyed in 2015 as the initial condition, bed sediment characteristics, and river discharge data from 2002–2007. Simulations were performed using the steady flow and sediment transport modules of HEC-RAS to predict riverbed changes for the period 2015–2018, and the results were validated using field measurements conducted in 2018. The simulation results indicate riverbed degradation of 0.08 m at SP.414 and 0.12 m at SP.257, while a relatively minor elevation change of 0.003 m was observed at SP.193. In contrast, field measurements show more pronounced scouring at SP.414 (0.38 m) and SP.257 (0.48 m), as well as sediment deposition of 0.56 m at SP.193. Validation using the Root Mean Square Error (RMSE) method indicates that the HEC-RAS simulation results exhibit a reasonably good level of agreement with field observations, particularly under average discharge conditions. This study demonstrates that flow discharge fluctuations play a critical role in controlling morphological changes in the Palu River, and that HEC-RAS modeling can serve as an effective supporting tool for sediment management and flood risk mitigation.